Studi Motivasi Golfer pada Golf Course sebagai Destinasi Wisata di Bandung dan Sekitarnya - Muhammad Iqbal Katik Rajoendah; Annisa Wardhani; Fauzi Mubarak; Firman Syah (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2023)
Decision-making by golf tourists in determining Bandung and its surroundings as a golf tourism destination is influenced by push factors that are intrinsic motivators. This article is a study to find out more about motivation of golfer in choosing Bandung and its surroundings as a golf tourism destination which is the area of research study, namely Dago Heritage 1917 Golf Course, Mountain View Golf Club, and Bandung Giri Gahana Golf & Resort. This verification research with descriptive-correlational method is done by using concurrent mix approach. Data analysis was performed using Statistics Package for Social Science (SPSS, Ver.23). Exploratory factor analysis is used to determine the level of correlation or relationship between variables within a factor in attribute motivation. Principal component analysis is used to determine the factor-forming variables in attribute motivation. Confirmatory factor analysis is used to confirm the results of this research analysis with previous research results which is a reference in this study. The principal component analysis yields 4 factors in motivation attributes, namely Relaxation and Togetherness, Destination Prestige, Benefits, and Business Opportunities. Previous research instruments are used in this study but the results of research in a study site cannot be generalized with other study sites.